Glucocorticoids in Patients with Rheumatic Diseases: Friends or Enemies of Bone? - Ciccarelli, Fedra; De Martinis, Massimo; Ginaldi, Lia (Current Medicinal Chemistry, 2015)
Increased bone resorption and enhanced risk of osteoporotic fractures are often reported in patients with diseases having immune system involvement, mainly inflammatory rheumatic diseases, for which glucocorticoids are more often prescribed because of their powerful antinflammatory effects. Among secondary osteoporosis, glucocorticoidinduced osteoporosis is the most common and severe form, and up to now prolonged glucocorticoid therapy has been considered the most important osteoporotic risk factor in rheumatic patients. However, it is now clear that the pathogenesis of osteoporosis in inflammatory rheumatic diseases is mediated by several factors. In particular, new discoveries within osteoimmunology concerning the complex relationship between bone and immunity, suggest that inflammation itself, through proinflammatory and osteoclastogenic cytokine overexpression, promotes bone resorption leading to increased skeletal fragility. Therefore, by controlling systemic inflammation, it is also possible to reduce the loss of bone mass which accompanies rheumatic diseases. From this point of view, we critically revisit the effects of glucocorticoids on bone in rheumatic diseases, in which they should be seen not just as an enemy of the bone health but eventually as a potential therapeutic tool capable of reducing the risk of osteoporosis by controlling disease activity and inflammation.
Keywords: rheumatic diseases